Elevating entrepreneurial satisfaction among young entrepreneurs through entrepreneurial education, economic literacy, adversity quotient, and creativity - Maulana Amirul Adha; Darma Rika Swaramarinda; Nova Syafira Ariyanti; Ayatulloh Michael Musyaffi; Rudy Ansar; Nina Farliana (Elsevier Ltd., 2025)
This study investigates the impact of entrepreneurial education, economic literacy, adversity quotient, and entrepreneurial creativity on the entrepreneurial satisfaction of young entrepreneurs in Indonesia. Using a quantitative approach with Structural Equation Modeling (SEM), the study surveyed 314 young entrepreneurs across various sectors. The findings reveal that entrepreneurial education significantly enhances economic literacy, adversity quotient, and creativity, all of which contribute positively to entrepreneurial satisfaction. Economic literacy and adversity quotient were found to be crucial in fostering creativity, leading to higher satisfaction levels among entrepreneurs. The study highlights the importance of integrating economic literacy and problem-solving skills into entrepreneurship education programs to better equip young entrepreneurs for business challenges. The results contribute to the literature by expanding the understanding of the relationship between these variables in the context of Indonesian entrepreneurship. Practical implications suggest that educational institutions and policymakers should focus on developing comprehensive entrepreneurship programs that include economic literacy and resilience-building components.